GAMBARAN SIKAP EMPATI ANAK KELOMPOK B1 DI TAMAN KANAK-KANAK ISLAM DAUD KHALIFATULLOH PADANG - Fuji Meilani; Izzati Izzati (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
Social ability is one aspect that must be owned by children, where with this social ability children will socialize with their surrounding environment. Empathy is an ability to understand and feel what is being experienced and thought by others. This research was conducted with the aim of knowing how to describe the empathy attitude of B1 children in Islamic Kindergarten Daud Khalifatulloh Padang. The research method was used in descriptive research with a qualitative approach. Data collection techniques in the form of observation, interviews, and documentation. The results of the study state that B1 children have a good empathy attitude, which is seen based on the aspects of empathy, such as cooperation, solidarity, tolerance, helping, compassion, caring, and tolerance